Design of MNU-Resilient latches based on input-split C-elements. (October 2021) - Huang, Zhengfeng; Li, Xiandong; Gong, Zhouyu; Liang, Huaguo; Lu, Yingchun; Ouyang, Yiming; Ni, Tianming
Abstract: With the continuous scaling of feature sizes, latches are becoming more and more sensitive to the multiple-node upsets (MNUs) induced by radiation. Based on input-split C-elements and a redundant feedback scheme, we propose a triple-node-upset-resilient latch (ISC-TRL) and a quadruple-node-upset-resilient latch (ISC-QRL) to provide high reliability. Using the novel interconnection scheme between the four-level input-split C-elements, any possible triple-node upset (TNU) or quadruple-node upset (QNU) occurred in the proposed latches can be filtered level by level, respectively. HSPICE simulation performed in 14 nm FinFET technology show that, compared with relevant MNU-hardened latches, the proposed ISC-TRL latch can reduce the delay-power-area product (DPAP) by 89.81% and only introduces 3.85% area overhead on average, while achieving 100% TNU-resilience and 99% QNU-resilience. The proposed ISC-QRL latch can reduce the DPAP by 83.01% and introduce 38.46% area overhead on average, while achieving 100% QNU-resilience. In addition, Monte Carlo simulation results show that the proposed ISC-TRL and ISC-QRL latches are of low sensitivity to process, voltage and temperature (PVT) variations.